PEMANFAATAN PATI UMBI UWI (DEOSCOREA ALATA) DAN LIMBAH JERAMI PADI (ORYZA SATIVA) SEBAGAI BAHAN BAKU ALTERNATIF BIOFOAM (BIODEGRADABLE FOAM) - Zulmanwardi; Irwan Sofia (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Styrofoam can trigger the transfer of styrene monomers into food, causing the risk of disease. To overcome this problem, alternative raw materials are used for environmentally friendly packaging, namely biodegradable foam or biofoam. Biofoam is made from starch. The properties of biofoam are the same as biodegradable plastic, in that it will be broken down by the activity of microorganisms into water and carbon dioxide if it is thrown into the environment. One source of starch is uwi tumber (Deoscorea alata). Research objectives: 1). Looking for optimum conditions for the ratio of starch from uwi tumbers to rice straw cellulose pulp, 2). Determining the heating temperature using the thermopressing method; 3). Test the water absorption capacity, tensile strength, biofoam breakdown period. Research method: stage I: Preparation of raw materials: 1). Production of uwi tumber starch. 2). making cellulose pulp from rice straw, and stage II: Making biofoam with a mixture of uwi tumber starch-cellulose pulp, and PVOH. Biofoam was analyzed for water absorption, tensile strength, and breakdown period. Conclusion: Optimal rice straw starch and cellulose ratio: 50% : 50%, heating temperature 200 °C, water absorption between 12.02-339.87%, tensile strength 0.6217 N/mm2, and decomposition period 14 days.